Cytomegalovirus as a Novel Target for Immunotherapy of Glioblastoma Multiforme - Schuessler, Andrea; Walker, David G.; Khanna, Rajiv (Frontiers in Oncology, 2014)
Progress in the treatment of glioblastoma multiforme (GBM) over the last few decades has remained marginal and GBM is still universally fatal with short survival times after initial diagnosis. Much research is focused on finding new therapeutics for GBM and immune based approaches have shown great promise. The detection of cytomegalovirus (CMV) antigens in malignant cells has suggested that treatment strategies based on immunological intervention, such as adoptive transfer of antiviral T cells or vaccination with viral epitopes, could be exploited as cancer therapy. We review here the rationale for using CMV as a therapeutic target and discuss the first clinical evidence for safety and efficacy of CMV specific cellular immunotherapy for GBM.